Cape Verdean Immigrants' Career Development and School Engagement: Perceived Discrimination as a Moderator. (August 2014) - Coutinho, Maria Teresa; Blustein, David L.
This study examined the contribution of perceptions of discrimination, career planning, and vocational identity to the school engagement experiences of first- and second-generation immigrants among a sample of 125 Cape Verdean high school students. Perceived ethnic discrimination was found to moderate the association between both vocational factors and school engagement. Students who perceived high levels of discrimination and endorsed a strong vocational identity also endorsed high levels of school engagement. When endorsing high levels of career planning, individuals reporting different levels of perceived discrimination did not differ in school engagement. However, large differences in school engagement were noted at low levels of career planning, with individuals reporting low levels of perceived discrimination endorsing higher engagement in school than those who perceived higher levels of discrimination. The findings highlight the importance of considering perceptions of ethnic discrimination as one explores the academic and vocational functioning of immigrant students of color.